2011
DOI: 10.4314/eajph.v7i1.64702
|View full text |Cite
|
Sign up to set email alerts
|

Hyperendemicity of onchocerciasis in Ovia Northeast local government area, Edo State, Nigeria.

Abstract: Background: Onchocerciasis is a chronic parasitic infection caused by the filarial nematode, Onchocerca volvulus. The objective of this study was to determine the prevalence, endemicity, and symptomatic effects of the disease in Ovia Northeast Local Government Area.Methods: The prevalence of onchocerciasis was investigated in Ovia Northeast Local Government Area of Edo State, Nigeria, between March 2008 and June 2009 using the standard skin-snip method. A total of 2020 subjects, who had visited various primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…One-way analysis of variance of the number of cases of the disease (prevalence) in the different Local Government Areas (L.G.As) shows that there is no significant difference in the prevalence rate of the disease in the L.G.As (P = 0.9986). Reports [15,16] show that the occurrence of Onchocerciasis varies from one geographical region to another and these zones belong to a common region. The prevalence of Onchocerciasis in Nigeria has significant variation in different villages with the villages that are near the breeding sites of vector showing higher infection prevalence [17].…”
Section: Resultsmentioning
confidence: 99%
“…One-way analysis of variance of the number of cases of the disease (prevalence) in the different Local Government Areas (L.G.As) shows that there is no significant difference in the prevalence rate of the disease in the L.G.As (P = 0.9986). Reports [15,16] show that the occurrence of Onchocerciasis varies from one geographical region to another and these zones belong to a common region. The prevalence of Onchocerciasis in Nigeria has significant variation in different villages with the villages that are near the breeding sites of vector showing higher infection prevalence [17].…”
Section: Resultsmentioning
confidence: 99%
“…The area was hyperendemic for onchocerciasis with a skin snip positivity rate of 83%. The prevalence of depigmentation was very high at 87.5%, itching was 84.16% and nodules 75.42% [20]. Another pre-control study in Anfilo District of West Wellega, Ethiopia used a multistage sampling technique and a total of 1114 individuals ≥ 15years were examined [21].…”
Section: Cutaneous Featuresmentioning
confidence: 99%
“…Compared with other parts of Nigeria, this area is notorious for entrenched onchocerciasis prevalence, presumably due to poor MDA coverage. [5][6][7][8] Precontrol nodule prevalence was 36.4%, and annual treatment began in mesoand hyperendemic villages in 1994 and continuously until 2016. 8 The five LGAs in question had nodule rates ranging from 42% to 62% and had microfiladermia as high as 83% in 2008/2009.…”
Section: Introductionmentioning
confidence: 99%
“…8 The five LGAs in question had nodule rates ranging from 42% to 62% and had microfiladermia as high as 83% in 2008/2009. 5 Recent surveys by African Programme for Onchocerciasis Control (APOC) and others have demonstrated persistent microfiladermia and ongoing transmission in this area. 9,10 For example, studies by APOC in 2010 showed continued high prevalence in Edo state, with 33.4% of participants positive by skin snip.…”
Section: Introductionmentioning
confidence: 99%